POSSIBILITIES OF ORGANIZING HUNTING TOURISM IN UZBEKISTAN - Shamsiyev Anvarjon (Research Parks Publishers, 2023)
The article presents opportunities for hunting tourism, which is gradually developing in my country, and highlights the feasibility of using these existing resources on a large scale. Development of the most expensive hunting species in terms of money is one of the most delicate and complex processes that take place along with awakening the spirit of true extreme hunters in tourists. Hunting tourism shall be carried out in compliance with ecological norms, not harming nature, and shall be under state control